Challenges of "Reverse" Aortic Arch Debranching for Repair of the Ascending Aorta by Thoracic Endovascular Aortic Repair. (2016) - Kansal, V.; Hadziomerovic, A.; Nagpal, S.
Abstract : Introduction: Ascending aortic pathology presents a unique challenge for treatment by thoracic endovascular aortic repair (TEVAR), because of lack of adequate endograft landing zones. This report describes a unique "reverse" extra-anatomical aortic arch debranching procedure performed to enable TEVAR of the ascending aorta. Report: A 71-year-old male presented with a large ascending aortic pseudoaneurysm secondary to previous arch repair anastomosis. This pathology was treated by TEVAR of the ascending aorta. To create a sufficient landing zone for the endovascular stent graft, a "reverse" extra-anatomical aortic arch debranching procedure was performed. This involved a left subclavian artery to left carotid artery bypass, left to right carotid-to-carotid bypass, ligation of proximal left common carotid artery, and embolization of the innominate artery origin. Discussion: TEVAR of the ascending aorta can be made feasible through a novel debranching procedure that creates sufficient landing zones for the endograft. This surgical approach may prove useful in patients who present with aortic arch pathology and comorbidities that prevent open surgical repair. Highlights: TEVAR of ascending aorta presents a challenge because of inadequate landing zones. Unique "reverse" extra-anatomic aortic arch debranching procedure is demonstrated. This technique enables TEVAR in patients with distal ascending aorta pathology.